2019
DOI: 10.1002/mds.27817
|View full text |Cite
|
Sign up to set email alerts
|

Sensory dysregulation in tic disorders is associated with executive dysfunction and comorbidities

Abstract: Background Tics are conceptualized as a sensorimotor phenomenon with a premonitory urge typically described by patients. As observed in other neurodevelopmental disorders, we have observed sensory dysregulation symptoms, such as tactile hypersensitivity to clothing, in children with tic disorders; however, formal clinical research in this area is limited. Objective To define the presence of sensory dysregulation symptoms in tic disorders, and their clinical associations. Methods Prevalence of sensory dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Sensory processing, meaning how sensory signals, such as light, sound, touch, taste or smell are perceived, are commonly altered in many neurodevelopmental disorders [ 1 , 2 ]. For example, sensory processing differences have been described in non-syndromic Autism Spectrum Disorders (ASDs) [ 3 ], tic disorders [ 4 ], Fragile X syndrome [ 5 ], attention deficit hyperactivity disorder [ 6 ] and a limited number of syndromic ASDs [ 7 , 8 , 9 , 10 ]. Not surprisingly, the specific sensory phenotypes and distributions of sensory differences vary across diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory processing, meaning how sensory signals, such as light, sound, touch, taste or smell are perceived, are commonly altered in many neurodevelopmental disorders [ 1 , 2 ]. For example, sensory processing differences have been described in non-syndromic Autism Spectrum Disorders (ASDs) [ 3 ], tic disorders [ 4 ], Fragile X syndrome [ 5 ], attention deficit hyperactivity disorder [ 6 ] and a limited number of syndromic ASDs [ 7 , 8 , 9 , 10 ]. Not surprisingly, the specific sensory phenotypes and distributions of sensory differences vary across diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sensory challenges directly impact the quality of life [ 14 ], and, therefore, appropriate counseling and early initiation of behavioral interventions can strongly impact patient and family experiences. Finally, many neurodevelopmental disorders have similar or overlapping presentations, and subtle clinical differences, such as sensory features, can be helpful in making a diagnosis or guiding genetic testing [ 3 , 4 , 15 ]. Thus, characterizing the sensory profiles for specific disorders is important for diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most children with ASD have an impaired sensory input, such as sound, touch, body movement/position, sight, taste, and smell; this results in a behavioral response to the sensory input experienced, which is called sensory processing (SP) difficulty. SP disorders are common in autism, with prevalence estimates of 90% [ 12 ], and they are associated with a wide variety of difficulties across many domains, that is, externalizing and internalizing behaviors; emotional and attention regulation; executive function; and daily-living functional activities, including social activities [ 13 , 14 ]. SP difficulties in children can have an impact on their participation in daily life activities and enjoyable tasks because of their atypical reactions to sensory stimuli and their impaired self-esteem [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…e CNN model is used in medical image processing to realize the intelligentization of lesion recognition, disease classification, and diagnosis [11]. And a large number of studies have confirmed this view [12].…”
Section: Introductionmentioning
confidence: 99%